A study of expression of estrogen and progesterone receptor, in atrophic, hyperplastic and malignant endometrial lesions, with emphasis on relationship with prognostic parameters - Kumari, Pasam Ramana; Renuka, Inuganti Venkata; Apuroopa, Murari; Chaganti, Padmavathi Devi (International Journal of Research in Medical Sciences, 2017)
Background: Aims of current study were to study the expression of estrogen receptor (ER) and progesterone receptor (PR) in atrophic, hyperplastic and malignant endometrial tissue, using immunohistochemical markers. Methods: The study includes 100 cases of endometrial tissues (25 cases each of atrophic and hyperplastic endometria and 50 cases of endometrial carcinomas). Results: In atrophic endometrial, 20 cases were ER and PR rich. 5 cases showed complete loss of hormone receptors (4 were type I and 1 type II). All the 25 cases of hyperplasias were ER and PR positive with varying H-score. The analysis of the hormone receptors in endometrial carcinomas, indicated that ER in 34 cases (68%) and of the PR in 38 cases (76%) were positive. Conclusions: Majority of the asymptomatic postmenopausal atrophic and hyperplastic endometria, expressed ER and PR. The value of the statistical significance was equal for atrophic vs. carcinomas and also hyperplastic vs. carcinomas. Positive ER PR expression was significantly associated with grade I-II and stage IB tumours. The correlation of immunohistochemical findings with histologic grade and clinical stage could help in predicting biologic behaviour and planning treatment in patients who are diagnosed as having these tumors.